Impact of Acid Concentration and Firing on the Long-term Bond Strength of a Zirconia-Lithium Silicate Ceramic Following Adhesive Cementation - Diniz, Vandeberg [UNESP]; Monteiro, Jaiane Bandoli [UNESP]; Meireles Rodrigues, Jonas Vinicius [UNESP]; Conde Oliveira Prado, Pedro Henrique [UNESP]; Melo, Renata Marques de [UNESP] (Quintessence Publishing Co Inc, 2019)
Purpose: To evaluate the effect of different firing stages (without firing, additional crystallization and glaze firings), hydrofluoric acid (HF) concentrations (5% and 10%), and thermocycling on the bond strength between resin cement and a zirconia-lithium silicate (ZLS) ceramic. Materials and Methods: ZLS ceramic (Celtra Duo, Dentsply Sirona) blocks were cut into smaller blocks and divided into 12 groups (N = 72), according to the HF concentration used, firing stage, and thermocycling (n = 6). All specimens were silanized (Monobond N, Ivoclar) and cemented with resin cement (Multilink N, Ivoclar) onto blocks of composite resin (Filtek Z250 XT, 3M). The specimens were immersed in distilled water for 24 h. The blocks were cut into sticks and tested immediately or thermocycled for 10,000 cycles in water (5 degrees C-55 degrees C). Microtensile bond strength (mu TBS) testing was then performed in a universal testing machine (0.5 mm/min, 50 kgf load cell). The failure modes of the sticks were examined using SEM and classified as adhesive, predominantly adhesive, or cohesive. Fracture surfaces were topographically evaluated using SEM. The 5% and 10% HF groups were analyzed separately and the data submitted to two-way ANOVA and Tukey's test (p < 0.05). Additional samples were used for SEM topographic analysis of representative ceramic surfaces. Results: The most frequent types of failure were predominantly adhesive between cement and ceramic and adhesive (cement completely covered the composite). Statistically significant differences were found only for the thermocycling factor (p < 0.05) for both HF concentrations. However, for the 10% HF groups, a marked decrease in mu TBS was observed after firing and thermocycling. SEM showed superficial irregularities on ZLS without etching, partial and total dissolution of the vitreous matrix and exposure of the crystals using 5% and 10% HF, respectively. Conclusion: The crystallization and glaze firings of ZLS ceramics conditioned with 5% HF promoted bond strength maintenance after thermocycling. Thermocycling decreased the bond strength in all groups, but mainly for fired ZLS conditioned with 10% HF.
Keywords: aging; bond strength; ceramic; firing; hydrofluoric acid; lithium silicate